A RETROSPECTIVE COHORT COMPARATIVE ANALYSIS OF CLINICAL CHARACTERISTICS AND ENDOSCOPIC FINDINGS IN SYMPTOMATIC DYSPEPSIA: RURAL VS. URBAN PATIENTS. - Guha, Shaibal (Student's Journal of Health Research Africa, 2024)
Background Symptomatic dyspepsia poses a significant burden on healthcare systems globally, with potential variations in clinical features and endoscopic findings between rural and urban populations. Understanding these differences is crucial for optimizing diagnostic and management strategies. Therefore, the study aimed to investigate and compare the clinical characteristics and endoscopic findings among symptomatic dyspepsia patients residing in rural and urban settings. Methods A retrospective study was carried out involving 120 individuals, aged 16 to 75 years, presenting with symptoms of dyspepsia, were included. Data collection involved reviewing medical records for patient demographics, clinical features, endoscopic findings, and histopathological results. Endoscopy was performed using standard protocols, and statistical analysis was conducted using SPSS version 24. Results The study comprised patients from both urban and rural areas, with a mean age of 45 years. Epigastralgia/epigastric burning was the most prevalent clinical feature (90%). Endoscopic examinations revealed inflammation (50%), erosions (35%), and reflux (30%) as the most common findings. No significant disparities were found in clinical features or endoscopic findings between rural and urban patients (p>0.05). Histopathological examination identified benign lesions in 80% of cases and malignant pathology in 20%, with no significant differences between rural and urban patients. Conclusion The study highlights the uniformity in clinical features, endoscopic findings, and histopathological results among symptomatic dyspepsia patients in rural and urban settings. These findings underscore the need for standardized diagnostic and management approaches, irrespective of geographical location. Recommendations Further research is warranted to explore additional factors contributing to dyspeptic symptoms and to evaluate the effectiveness of tailored interventions based on geographical and demographic factors.